Dyes removal from textile wastewater by agricultural waste as an absorbent – A review - Farah Amalina, Ishak; Abdul Syukor, Abd Razak; Krishnan, Santhana; Zularisam, Abdul Wahid; Mohd, Nasrullah (Elsevier B.V., 2022)
Water pollution from the textile industry affects environmental conditions by generating large-scale effluent mixed with various dyes. Dyes are mostly organics with multiple compound structural and molecular weight variations; if not managed properly before release, they may harm the environment and organism. However, many dyes are categorized into distinct groups, and various adsorbents for dye adsorption have been identified. Among these dyes, methyl dyes, which come in multiple colours, are the most popular in research due to their availability and accessibility. It is imperative to use effective treatments using special adsorbents to remediate water contamination before discharging into streams. As awareness of environmental issues increases with time, the need for a wide range of adaptive alternative feedstock that satisfies ecological regulations has become a priority for researchers worldwide. Therefore, there is a need to develop other adsorbents from alternatively economic raw materials such as locally available industrial and mineral waste and by-products. Additionally, numerous materials have been used, prepared, or grafted from various agricultural peel-based adsorbents. Biomass is a significant source of renewable adsorption processes for hazardous compounds, including toxic organics and metals/elements. It is much cheaper, has abundance, effective adsorption capability, and reusability, have numerous advantages over conventional materials. This review focuses on using plant agricultural wastes to remove dyes. Different adsorption capacities, operating conditions, and application forms have been investigated. The adsorption kinetics and isotherms are demonstrated to illustrate the adsorbent's properties and adsorption mechanisms.